CHALLENGES OF USING TRANSBOND PLUS IN ORTHODONTIC TREATMENT - Eugen Silviu Bud; Stanca Ioana Bucur; Dorin Ioan Cocoș; Sorana Maria Bucur; Anamaria Bud; Alexandru Vlasa (Romanian Society of Oral Rehabilitation, 2021)
Aim of the study. This in vitro study aimed to investigate the shear bond force created by Transbond Plus Color Change and Transbond Self-Etching Primer in different conditions of the primer's application and for different durations of light-curing the bonding agent. Material and methods. The study sample consisted of 48 premolars extracted for orthodontic purposes. The teeth were divided into four groups each one of 12 premolars then the brackets were bonded in each group by different procedures: in groups 1 and 2 by the classical application of the primer followed by the light-curing of the bonding agent for 20 and 40 seconds, respectively. In groups 3 and 4 the primer was light-cured then the bonding agent was cured for 20 and 40 seconds, respectively. We used a universal testing machine for detaching the brackets and determined the SBS's values. Results. The mean SBS's values in groups 1, 2, 3 and 4 were 12.23, 15.93, 15.35 and 18.49. We found statistically significant differences between groups.